Determination of Pentacyclic Triterpenoids in Plant Biomass by Porous Graphitic Carbon Liquid Chromatography—Tandem Mass Spectrometry - Ilya S. Voronov; Danil I. Falev; Anna V. Faleva; Nikolay V. Ul’yanovskii; Dmitry S. Kosyakov (Molecules, 2023)
Pentacyclic triterpenoids (PCTs), which possess a number of bioactive properties, are considered one of the most important classes of secondary plant metabolites. Their chromatographic determination in plant biomass is complicated by the need to separate a large number of structurally similar compounds belonging to several classes that differ greatly in polarity (monools, diols, and triterpenic acids). This study proposes a rapid, sensitive, and low-cost method for the simultaneous quantification of ten PCTs (3β-taraxerol, lupeol, β-amyrin, α-amyrin, betulin, erythrodiol, uvaol, betulinic, oleanolic, and ursolic acids) by high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) using porous graphitic carbon (Hypercarb) as a stationary phase capable of hydrophobic retention and specific interactions with analytes. Revealing the effects of the mobile phase composition, pH, ionic strength, and column temperature on retention and selection of chromatographic conditions on this basis allowed for the effective separation of all target analytes within 8 min in gradient elution mode and attaining limits of detection in the range of 4–104 µg L−1. The developed method was fully validated and successfully tested in the determination of PCTs in common haircap (Polytrichum commune) and prairie sphagnum (Sphagnum palustre) mosses, and fireweed (Chamaenerion angustifolium) stems and leaves.